NIH Toolbox Cognition Battery (CB): Validation of Executive Function Measures in Adults - Zelazo, Philip David (J Int Neuropsychol Soc, 2014)
This study describes psychometric properties of the NIH Toolbox Cognition Battery (NIHTB-CB) executive function measures in an adult sample. The NIHTB-CB was designed for use in epidemiologic studies and clinical trials for ages 3 to 85. A total of 268 self-described healthy adults were recruited at four university-based sites, using stratified sampling guidelines to target demographic variability for age (20–85 years), gender, education and ethnicity. The NIHTB-CB contains two computer-based instruments assessing executive function: the Dimensional Change Card Sort (a measure of cognitive flexibility) and a flanker task (a measure of inhibitory control and selective attention). Participants completed the NIHTB-CB, corresponding gold standard convergent and discriminant measures, and sociodemographic questionnaires. A subset of participants (N = 89) was retested 7 to 21 days later. Results reveal excellent sensitivity to age-related changes during adulthood, excellent test–retest reliability, and adequate to good convergent and discriminant validity. The NIH Toolbox EF measures can be used effectively in epidemiologic and clinical studies.